Assessing the effective use of mosquito nets in the prevention of malaria in some parts of Mezam division, Northwest Region Cameroon. (December 2016) - Ntonifor, Ngum; Veyufambom, Serophine
Abstract Background In Cameroon, malaria continues to be endemic and the first major cause of morbidity and mortality among the most vulnerable groups—children under 5 years of age, pregnant women, people living with HIV/AIDS and the poor. The use of long-lasting insecticide-treated bed nets (LLINs) is one of the recommended measures to prevent malaria. The present study was aimed at accessing the acceptability and effective use of LLINs on the prevalence of malaria in PMI Nkwen, Bambui and its environs. Methods Hospital-based diagnosis consisted of 476 blood samples that were screened using the rapid diagnostic kits to determine the prevalence of malaria among users and non-users of LLINs. A structured questionnaire was also administered to pregnant women and children less than 5 years of age (476 hospital-based and 350 from the community) which consisted of demographic information, availability, accessibility affordability, acceptability, effective use and problems encountered with the use of LLINs. Results Result obtained showed that out of the 476 hospital-based patients, 29 tested positive for malaria giving an overall prevalence of 6.09 %. Equally, results of the questionnaire showed that 743 (89.9 %) of the respondents owned LLINs with up to 649 (87.3 %) having been given to them free-of-charge, and that 578 (77.8 %) were using their LLINs to sleep, even though 18.2 % of the respondents used their LLINs for other purposes, such as fishing, nursing seeds and footfall nets. Malaria was minimal among users of LLINs than non-users and the results were significant at P ≤ 0.05. Also 71.9 % of the respondents said that their nets were in good condition while 52.2 % of them said the major problem with the usage of LLINs was heat and the feeling of suffocation. Conclusion These results indicate that LLINs have significantly reduced the prevalence of malaria among the studied population, and so the government should not relent its efforts in the distribution of these nets especially to the vulnerable groups in order eliminate malaria and other mosquito-borne diseases. Utilization of LLINs needs to be encouraged to match ownership, while free distribution of ITNs to vulnerable groups needs to be continuous and consistent.